The Impact of Customer Experience toward Customer Satisfaction and Loyalty of Ciputra World Surabaya - Silvana Chandra (iBuss Management, 2014)
Ciputra World Surabaya is facing a tense competition, especially with the upcoming new shopping malls. Author believes that customer satisfaction and loyalty is the ultimate solutions to maintain the visitors traffic, which can be achieved by encouraging customer experience. The research succeeds to gather 142 respondents using simple random sampling method. Thus, by applying the Path Analysis with Regression, it is able to prove that customer experience has significant impact toward customer satisfaction of Ciputra World Surabaya. Then, customer satisfaction has significant impact toward customer loyalty of Ciputra World Surabaya. Author also tested customer satisfaction as mediating variable, however, the result shows that customer experience has no significant impact toward customer loyalty, mediated by customer satisfaction of Ciputra World Surabaya. Keywords: Customer Experience,Customer Satisfaction, Customer Loyalty, Ciputra World Surabaya